Study guide for Stiglitz's principles of macroeconomics - Martin, Lawrence W. (W. W. Norton, 1997)
This book is divided into five parts: Introduction, Full-Employment macroeconomics; Unemployment macroeconomics; Dynamics and macro policy; and Issues in macroeconomic policy.